1995
DOI: 10.1159/000106939
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Analysis of Dementia in a Japanese Leprosarium

Abstract: In a neuropathological study of consecutive autopsies, prevalence and cause of dementia in a Japanese leprosarium were investigated, where more than 95% of inpatients with a mean age of 70 years are now free from active leprosy. In 10 years (1983–1992), clinically overt dementia at death was 35/136 (25.7%) in the age group over 65 years (mean age 79.4). Autopsy was performed in 85 cases (mean age 81 years), and clinically overt dementia was seen in 25 subjects (29.4%). Neuropathologically, Alzheimer''s disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Previous epidemiological studies have shown that elderly people with leprosy treated by antileprosy drugs had a significantly lower incidence of dementia compared with drug‐free patients, although there is some controversy . Namba et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological studies have shown that elderly people with leprosy treated by antileprosy drugs had a significantly lower incidence of dementia compared with drug‐free patients, although there is some controversy . Namba et al .…”
Section: Discussionmentioning
confidence: 99%
“…The literature regarding dementia in leprosy patients is limited, and the results are controversial. Compared with the general population, an epidemiology study revealed that the population of leprosy patients had a significantly low prevalence rate of senile dementia, from 2.9% to 6.25% (McGeer et al , ), but other studies have indicated that leprosy patients in leprosariums have a higher‐than‐normal rate of senile dementia, at 16.8–20.7% (Goto et al , ; Endoh et al , ). The differing results might have been due to the bias arising from the sampling of different research settings.…”
Section: Discussionmentioning
confidence: 99%
“…According to conflicting reports by the Japanese Sanatorium for leprosy patients, Hansen's disease was a factor in reducing the incidence of Alzheimer's disease [6]. In addition, the Japanese researchers tested dapsone-containing medicines for leprosy patients, but they were unable to find the effect of removing amyloid beta protein; thus, they proposed that Mycobacterium leprae is a major causative factor of Hansen's disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Japanese researchers tested dapsone-containing medicines for leprosy patients, but they were unable to find the effect of removing amyloid beta protein; thus, they proposed that Mycobacterium leprae is a major causative factor of Hansen's disease [7]. Worldwide, M. leprae is considered responsible for reducing the incidence of Alzheimer's disease based on these two papers [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation